Analysis of Spatial Skills Impact of Science, Technology, Engineering, And Mathematics (STEM) Approach in Cartography Learning - Sari, Ulfi Andrian; Rizki, Kamalia Fitri; Pujianti, Berlinda (JURNAL GEOGRAFI, 2024)
The independent campus curriculum is an effort to increase competition in the 21st century, which requires competent human resources in the fields of science, technology, engineering and mathematics (STEM). STEM learning responds to the need to increase students' interest and skills in these areas. This study aims to determine the effect of using the STEM approach on spatial thinking skills in cartography learning. This research uses a quasi-experimental method with a one-group pretest-posttest Design, conducted in a single experimental class without a control class. Subjects were selected by random sampling through drawing lots, focusing on 5th-semester B students. Data were analysed using a t-test with paired samples T-Test. The results showed a sig value. (2-tailed) of 0.000, which is smaller than the significance value of 0.05. Therefore, H0 is rejected, and Hâ‚ is accepted. To conclude, there is an increase in the average pretest and posttest after learning using the STEM approach, indicating that the STEM approach positively affects spatial thinking skills. Each stage of the STEM approach affects the students' spatial abilities. The science stages develop spatial abilities in the form of spatial interaction. The technology stages enhance the ability to apply applications and scale on maps. The engineering stage fosters analytical, representative and comprehensive skills. The math stage improves the ability to calculate scale and its application in everyday life.Keywords: spatial skills, STEM, cartography